LEARNING AND TEACHING MULTIPLE LANGUAGES (Educa Journal of Studies, 2026)
Mastering in languages bring numbers of profits to both individuals’ and academic perception. In this paper we examine the learning and teaching procedure of several languages. This research discusses and will have specific attention respectively to the 1st benefits of multilingualism, 2nd how to be multilingual, 3rd the rules of teaching and 4th challenges also negative sides of being bilingual for the brain in the discussion part. The authors attempt to address the brain working, cognitive reserve, problem-solving and how learning multiple languages affect to people’s mindsets. Although this research highlights the learning tips, it concentrates methods of teaching a language in a more impactful, with strong impression, and accessible through applying the long-term memory. To achieve accurate criteria and addressing the technical challenges, we applied questionnaires and collected data through a survey which has been analysed and represented the grounded results to give us a better understanding of our concerns.
Keywords: Multilingualism, Language Acquisition, Cognitive Benefits, Language Pedagogy, Long-Term Memory.